PELVIC INFLAMMATORY DISEASE (PID): A COMPREHENSIVE CLINICAL (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Pelvic inflammatory disease (PID) represents a spectrum of infectious and inflammatory disorders affecting the upper female genital tract, encompassing the uterus, fallopian tubes, ovaries, and adjacent pelvic structures . Characterized primarily by ascending spread of microorganisms from the lower genital tract, PID remains one of the most consequential reproductive health conditions among women of reproductive age worldwide.